Sabermetrics Baseball, Steroids, and How the Game has Changed Over the Past Two Generations - Costa, Gabriel B.; Costa, Gabriel B. (Elsevier Science, 2021)
Sabermetrics: Baseball, Steroids, and How the Game has Changed Over the Past Two Generations offers an introduction to this increasing area of interest to statisticians, students of the game, and many others. Pairing a primer on the applied math with an overview of the origin of the field and its context within baseball today, the work provides an engaging resource for students and interested readers. It includes coverage of relevant baseball history, Bill James and SABR, broken records and steroids. Drawing on the author$1 (Bs experience teaching the subject at Seton Hall University since 1988, Sabermetrics also offers practice questions and solutions for class use. Provides an accessible, brief introduction to the practice of sabermetrics Approaches the topic in context with recent trends and issues in baseball Includes questions and solutions for math practices